SciVee 2008
DOI: 10.4016/5368.01
|View full text |Cite
|
Sign up to set email alerts
|

Homogenization of northern U.S. Great Lakes forests due to land use

Abstract: Human land use of forested regions has intensified worldwide in recent decades, threatening long-term sustainability. Primary effects include conversion of land cover or reversion to an earlier stage of successional development. Both types of change can have cascading effects through ecosystems; however, the longterm effects where forests are allowed to regrow are poorly understood. We quantify the regionalscale consequences of a century of Euro-American land use in the northern U.S. Great Lakes region using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 18 publications
(31 reference statements)
3
64
0
1
Order By: Relevance
“…Alterations of disturbance regimes in concert with habitat degradation can lead to a loss of ecosystem diversity. There is growing evidence for the homogenization of northern Great Lakes forests via conifer loss (Frelich & Lorimer, 1985;Rhemtulla et al, 2007;Schulte et al, 2007;Nowacki & Abrams, 2008). Northern Wisconsin forests were historically dominated by conifer and mixed conifer-hardwood stands (Schulte et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations of disturbance regimes in concert with habitat degradation can lead to a loss of ecosystem diversity. There is growing evidence for the homogenization of northern Great Lakes forests via conifer loss (Frelich & Lorimer, 1985;Rhemtulla et al, 2007;Schulte et al, 2007;Nowacki & Abrams, 2008). Northern Wisconsin forests were historically dominated by conifer and mixed conifer-hardwood stands (Schulte et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence for the homogenization of northern Great Lakes forests via conifer loss (Frelich & Lorimer, 1985;Rhemtulla et al, 2007;Schulte et al, 2007;Nowacki & Abrams, 2008). Northern Wisconsin forests were historically dominated by conifer and mixed conifer-hardwood stands (Schulte et al, 2007). Because of intense deforestation and resultant fires after Euro-American settlement, old growth forest types decreased in abundance and were replaced by early successional forest types (Rhemtulla et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Once the Cutover had cleared large swaths of these forests, the logging industry waned, resulting in a mass migration of workers from the region that would not revive until the post-WWII planting of successional forests for recreation, wise use, and restoration (Rhemtulla et al 2009). Today, as a result of post-Depression-era public land designations in the 1940s, forestry and restoration have resulted in a patchwork of homogenous coniferous and deciduous stands (Radeloff et al 1999, Schulte et al 2007.…”
Section: Study Area and Historymentioning
confidence: 99%
“…Biomass-weighted estimates of forest composition are based on Public Land Survey System (PLSS) records (Schulte et al 2007, Liu et al 2011, Goring et al 2016, Cogbill et al 2018 and United States Forest Service Forest Inventory and Analysis (FIA) data (Forest Inventory Analysis Program 2007, Gray et al 2012). PLSS records provide an estimate of mid-to late-1800s forests, while FIA observations are from the most recent full plot inventory (2007)(2008)(2009)(2010)(2011) (Goring et al 2016).…”
Section: Forestry Datamentioning
confidence: 99%
“…In a region close to the present study, Ziter et al (2014) found that carbon storage was robust to both management and edge effects (but see Isbell et al (2015)). However, the homogenizing effects of forest management and use on community composition (Schulte et al, 2007;Thompson et al, 2013) might eliminate or reduce the relative abundance of species that can contribute to the provisioning of other vital ecosystem functions, including nutrient cycling, pollination or seed dispersal, and associated ecosystem services (Mitchell et al, 2014). It can also affect the ability of the ecosystem to resist or adapt to unknown disturbances such as forest pests and pathogens (Boyd et al, 2013) or invasion by alien plant species (Tanentzap et al, 2010) that could negatively affect the dominant species.…”
Section: Ecological Resilience and Functional Composition Across Privmentioning
confidence: 99%